KEMAMPUAN PEMAHAMAN KONSEP SEGI EMPAT SMP MELALUI PEMBELAJARAN INQUIRY - Rahmatia Rahmatia; Ipung Yuwono; Swasono Rahardjo (Jurnal Kajian Pembelajaran Matematika, 2018)
This study aimed at describing students’ comprehension toward four square concepts through inquiry learning. This study engaged descriptive-qualitative method which involve seven gradrers of SMPN 3 Satu Atap Dulupi as the participants.This study acknowledged students’ concept comprehension competence consists of: (1) re-stating the concept, (2) using, utilizing, and choosing the prcedures, and (3) apllying the concept in problem solving. The findings of the study showed that the students were able to comprehend the concepts of four square through inquiry learning.Therefore, the inquiry learning can be used as an alternative in the mathematics learning process in Junior High Schools.